2020
DOI: 10.2169/internalmedicine.4399-19
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Frailty and Abdominal Symptoms: A Hospital-based Cross-sectional Study

Abstract: Objective The association between frailty and abdominal symptoms has not been evaluated. Methods We conducted a hospital-based, retrospective cross-sectional study of consecutive outpatients ≥65 years old at the Department of Gastroenterology, Juntendo Tokyo Koto Geriatric Medical Center from 2017 to 2019. Patients were included in the study if all of the following information was available from their medical records: patient's profile, the evaluation of osteoporosis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…OP, risk of falls, and SP were reported in the I‐Lan Longitudinal Aging Study to be associated with frailty independently 37 . In a hospital‐based study, SP was strongly associated with frailty ( P < 0.001) while relationships with OP were weaker ( P = 0.055) 38 . Finally, in a retrospective study among postmenopausal patients with known OP attending a hospital bone clinic, those with a diagnosis of osteosarcopenia were more likely to be frail than those with OP alone 25 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…OP, risk of falls, and SP were reported in the I‐Lan Longitudinal Aging Study to be associated with frailty independently 37 . In a hospital‐based study, SP was strongly associated with frailty ( P < 0.001) while relationships with OP were weaker ( P = 0.055) 38 . Finally, in a retrospective study among postmenopausal patients with known OP attending a hospital bone clinic, those with a diagnosis of osteosarcopenia were more likely to be frail than those with OP alone 25 …”
Section: Discussionmentioning
confidence: 97%
“…37 In a hospital-based study, SP was strongly associated with frailty (P < 0.001) while relationships with OP were weaker (P = 0.055). 38 Finally, in a retrospective study among postmenopausal patients with known OP attending a hospital bone clinic, those with a diag-nosis of osteosarcopenia were more likely to be frail than those with OP alone. 25 As expected, frailty and pre-frailty were more prevalent in individuals over the age of 80 in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding 203 articles, a total of 49 articles (including the 2 articles identified by the manual search) were included in the scoping review ( Figure 1 ). Those articles were then categorized as those in which Zn intake was assessed (n = 30), 16–29 , 31–46 serum or tissue Zn levels (n = 18), 47–64 or both (n = 1). 30 Two articles included different findings from the same study sample 54 , 64 ; these findings were reported in combination in this review ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“… 50 The studies were conducted primarily in Europe (n = 18), 17 , 18 , 22 , 26 , 28 , 29 , 32 , 33 , 41–43 , 46 , 48 , 51 , 56 , 58–60 15 were conducted in Asia. 23 , 24 , 27 , 30 , 35 , 36 , 38 , 39 , 45 , 47 , 49 , 57 , 61 , 63 , 64 Seven studies each were from North America 19 , 25 , 31 , 44 , 52 , 53 , 62 and Australasia, 20 , 21 , 37 , 40 , 50 , 54 , 55 and the remaining 2 studies were from Jordan 16 and Turkey. 34 …”
Section: Resultsmentioning
confidence: 99%
“…We thought that the lack of collagen and the effect of inflammatory factors might play important roles in it [18][19][20]. Furthermore, the appearance of GERD symptoms limits the patient's physical activity ability [21], and abdominal symptoms affect the patient's nutritional intake to some extent [22]. Muscle wasting and insufficient nutrition could lead to a loss of skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%